1994
DOI: 10.1007/bf02167903
|View full text |Cite
|
Sign up to set email alerts
|

Mother-child interactions in ADHD and comparison boys: Relationships with overt and covert externalizing behavior

Abstract: Reciprocal relationships between child characteristics and such familial factors as parental psychopathology and interaction style with the child characterize the development and maintenance of attention-deficit hyperactivity disorder (ADHD) as well as its comorbidity with antisocial behavior. Our goal was to ascertain the ability of negative maternal behavior exhibited during mother-son interactions to predict independently observed overt and covert externalizing behavior in the child, controlling for current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
55
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 37 publications
9
55
0
Order By: Relevance
“…During the summer research program, we also investigated ADHD children's responses to methylphenidate. Other research utilizing this sample is reported in Anderson, Hinshaw, and Simmel (1994); Hinshaw, Simmel, and Heller (1995);and Nigg, Swanson, and Hinshaw (1996).…”
Section: Methodsmentioning
confidence: 86%
“…During the summer research program, we also investigated ADHD children's responses to methylphenidate. Other research utilizing this sample is reported in Anderson, Hinshaw, and Simmel (1994); Hinshaw, Simmel, and Heller (1995);and Nigg, Swanson, and Hinshaw (1996).…”
Section: Methodsmentioning
confidence: 86%
“…Percentage of agreement among raters for these two categories is: NC = .70 and physical/verbal aggression = .60 (Hinshaw, 2002). This system has received extensive validation in terms of known-groups validity , as an indicator of medication response (Hinshaw et al, 1989), as a predictor of initial sociometric impressions (Erhardt & Hinshaw, 1994), and as a criterion measure for the effects of parenting behavior (Anderson et al, 1994).…”
Section: Baseline Measuresmentioning
confidence: 99%
“…ADHD is believed to have multiple etiologies, many of which are biologically based and include genetic factors (see Barkley, 1998, for a review of studies). However, the expression of problems associated with ADHD, for example oppositional behavior, appears to have a strong relationship with social or environmental factors as well (Anderson, Hinshaw, & Simmel, 1994;August, Realmuto, Joyce, & Hektner, 1999;Barkley, 1998;Campbell, Breaux, Ewing, & Szumowski, 1986;Johnston & Mash, 2001). In particular, it has been argued that the development of oppositional behavior in children with ADHD is related to family variables such as coercive parenting and parental psychopathology (Moffitt, 1990;Whalen & Henker, 1999; see also Carlson, Tamm, & Hogan, 1999, for a review of studies).…”
mentioning
confidence: 95%
“…Elements of parenting responsiveness, such as negative affect, have been found to predict oppositional behavior in boys with ADHD even with the effects of child negative behavior and maternal psychopathology controlled (Anderson et al, 1994). Some studies find that maternal insensitivity, intrusive parenting, and negative affect in infancy or the preschool years are predictors of both hyperactive and aggressive behaviors in school-aged children (Campbell et al, 1986;Campbell, Pierce, Moore, Marakovitz, & Newby, 1996;Carlson et al, 1995); however, other longitudinal research suggests that, after controlling for the effects of infant and family risk factors, the absence of maternal responsiveness in infancy predicts children's subsequent oppositional behavior, but not ADHD symptoms (Wakschlag & Hans, 1999).…”
mentioning
confidence: 99%